Insecticides, Miticides & Molluscicides Available to Florida's Floricultural Industry - James F. Price; Curtis Nagle; Elzie McCord, Jr. (EDIS)
This document is ENY-679, one of a series of the Entomology & Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2003.